Clever use of natural clay materials in the synthesis of non-symmetric carbonates by utilizing CO2 as a feedstock: Ag/attapulgite nano-catalyst. Issue 29 (16th July 2020) - Guo, Ruixiang; Wang, Gang; Liu, Weisheng
Abstract : We design a heterogeneous catalyst by taking advantage of the unique structure of Attapulgite and its ability to absorb CO2, Ag/Attapulgite Nano-catalyst, which has high activity and stability in in the CO2 fixation reaction. Abstract : Using natural minerals seems to be one of the most novel and environmentally friendly strategies to design catalysts for CO2 conversion. Herein, we report a facile and efficient nano-catalyst for the synthesis of non-symmetric carbonate by utilizing a magnesium-aluminium silicate nano-mineral—attapulgite (ATP). Thanks to the unique structure of ATP and its ability to absorb carbon dioxide, the Ag/attapulgite nano-catalyst has excellent catalytic activity and stability in the carbon dioxide fixation reaction. The design of this Ag/attapulgite nano-catalyst provides a novel idea for realizing CO2 conversion and clay resource utilization.